2020
DOI: 10.1038/s41598-020-73592-1
|View full text |Cite
|
Sign up to set email alerts
|

Bovine sperm-oviduct interactions are characterized by specific sperm behaviour, ultrastructure and tubal reactions which are impacted by sex sorting

Abstract: To date sperm-oviduct interactions have largely been investigated under in vitro conditions. Therefore we set out to characterize the behaviour of bovine spermatozoa within the sperm reservoir under near in vivo conditions and in real-time using a novel live cell imaging technology and a newly established fluorescent sperm binding assay. Sperm structure and tubal reactions after sperm binding were analysed using scanning and transmission electron microscopy and histochemistry. As a model to specify the impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 93 publications
0
28
0
Order By: Relevance
“…Likely, these signaling molecules will either act to break bonds of the cell body with the wall or bind to the flagellum and initiate a different beat form that will aid in generating increased force to break away from the wall [18,19]. There are many interesting and unanswered questions as to how sperm get to the walls, how long they stay at the walls, as well as how the sperm reservoir could act as a filter to sort out healthy sperm [20,21]. Investigations with microfluidic channels have revealed that sperm guidance can be achieved with surface topography and microchannels [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Likely, these signaling molecules will either act to break bonds of the cell body with the wall or bind to the flagellum and initiate a different beat form that will aid in generating increased force to break away from the wall [18,19]. There are many interesting and unanswered questions as to how sperm get to the walls, how long they stay at the walls, as well as how the sperm reservoir could act as a filter to sort out healthy sperm [20,21]. Investigations with microfluidic channels have revealed that sperm guidance can be achieved with surface topography and microchannels [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, sperm motility is preserved in the sperm reservoir and is sustained by the molecular interactions with the oviduct and secretions such as glycoproteins and acidic mucopolysaccharides, which are produced by the secretory cells of the tubal epithelium 16 . LCI revealed that 5%–15% of the sperm in the reservoir reveal hyperactivation.…”
Section: The Sperm Reservoirmentioning
confidence: 99%
“…LCI revealed that 5%–15% of the sperm in the reservoir reveal hyperactivation. They show an asymmetrical high amplitude and a whip‐like beating of the tail and a rotating head 16 . Hyperactivation is an important key behavior of sperm, which allows them to detach from the tubal epithelium and to penetrate the cumulus oophorus of the oocyte after ovulation 39,40 .…”
Section: The Sperm Reservoirmentioning
confidence: 99%
See 1 more Smart Citation
“…Sperm binding assays often only measure binding capacity to a single glycoprotein or ligand and do not take the multi-molecular nature of sperm-oviduct interactions into account [27]. Monolayers of ciliated epithelial cells lack the 3D orientation of the oviductal folds [28], the response of secretory cells to sperm binding [29] and paracrine signaling between neighboring cells [30]. In a similar manner, spheroid explants do not accurately replicate the scaffolding anatomy of the oviduct [28].…”
Section: Introductionmentioning
confidence: 99%